Evaluation of Open-Source Online Dictionaries - Crnec, Dina; Seljan, Sanja (2010)
The paper stresses the importance of promoting multilingualism in today's society and the symbiosis of technology and education in general. The emphasis is put onto necessity for development of online dictionaries of open-source type as a part of language technologies, seen through the aspect of tools for translation and language learning. The objectives of the study are as follows: comparative analysis and evaluation of Croatian-English and English-X dictio-naries according to specific quality rank, series of questions related to examinees' previous education – place and pre-ferred ways of education, and finally, examinees' self-evaluation of four language skills according to the European language levels Self Assessment Grid. The research was conducted among the students of information sciences at the Faculty of Humanities and Social Sciences, University of Zagreb, using the method of survey. The results have been analyzed and further recommendations and guidelines given.
Projekt MZOS
ENG